Primeiro registro de Strongyloides sp. (Nematoda, Strongyloididae) em Lutreolina crassicaudata (Didelphimorphia: Didelphidae) - Cardia, D. F.F.; Camossi, L. G. [UNESP]; Fornazari, F. [UNESP]; Babboni, S. D.; Teixeira, C. R. [UNESP]; Bresciani, K. D.S. [UNESP] (FapUNIFESP (SciELO), 2016)
The present study reports the first case of the presence of the intestinal nematode Strongyloides sp. in fecal examinations of a male Lutreolina crassicaudata, considered a synanthropic marsupial species with zoonotic potential. The Willis technique was used for the diagnosis. Presence of typical eggs of Strongyloides species in feces was detected. A fecal culture was performed to obtain larval stages, free-living adults and infective third stage larvae (L3) of this nematode after seven days, which was morphologically identified as Strongyloididae. This is the first report of infection by Strongyloides sp. in a tick-tailed opossum from Brazil.
First report of Strongyloides sp. (Nematoda, Strongyloididae) in Lutreolina crassicaudata (Didelphimorphia: Didelphidae)
Keywords: Helminth; Nematoda; Opossum; Strongyloides